(untitled) (Jurnal Pelita Pendidikan, 2016)
This study was aimed to analyze the student™s misconception on human circulatory system topic and also to determine the effectivity of interactive multimedia to reduce students misconception that experienced by students of XII IPA grade in SMA Negeri 1 Berastagi. The study consisted of two parts. Firstly is descriptive to investigate student™s misconception on human circulatory system topic. Secondly quasi experimental research used after learning process. Quasi experimental research used to determine the effectivity of interactive multimedia in reducing student™s misconception. The experimental used one group pretest and posttest design. Instrument that used for detecting students misconception were two dimensional diagnostic test and essay test, for reducing students misconception by using interactive multimedia as learning media. Student™s misconception reduce 42.46% in group that using interactive multimedia as learning media and reduce 14.8% in group without interactive multimedia. Based on the calculation, it was got 0.57 as gain index value in group that using interactive multimedia and 0.30 as gain index value in group without interactive multimedia. The ttest result was tcount (6.598) and ttable (1.699), so tcount (6.598) > ttable (1.699). It was conclude that interactive multimedia is effective to reduce student™s misconception on human circulatory system in SMA Negeri 1 Berastagi Class XII IPA A.Y. 2016/2017. Keywords: Misconception, Students™ Misconception, Human Circulatory System